2016
DOI: 10.1111/ggi.12708
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging signatures of frailty: A population‐based study in community‐dwelling older adults (the Atahualpa Project)

Abstract: Neuroimaging signatures of frailty are mainly related to age. This reinforces the importance of early frailty detection to reduce its catastrophic consequences. Geriatr Gerontol Int 2017; 17: 270-276.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 25 publications
1
53
0
Order By: Relevance
“…Quantification of global and regional brain atrophy as an MRI marker for neurodegenerative diseases is widely performed in research on cognitive impairment and dementia ( Mak et al., 2015 , Verlinden et al., 2017 ). However, only few studies have performed these analyses in relation to frailty ( Chen et al., 2015 , Del Brutto et al., 2017 ). These studies included a low number of frail individuals and thus combined prefrail and frail individuals in 1 group, possibly reducing the contrast between groups ( Chen et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantification of global and regional brain atrophy as an MRI marker for neurodegenerative diseases is widely performed in research on cognitive impairment and dementia ( Mak et al., 2015 , Verlinden et al., 2017 ). However, only few studies have performed these analyses in relation to frailty ( Chen et al., 2015 , Del Brutto et al., 2017 ). These studies included a low number of frail individuals and thus combined prefrail and frail individuals in 1 group, possibly reducing the contrast between groups ( Chen et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…WMHs are related to cognitive decline and physical deterioration such as gait problems ( De Laat et al., 2011 , Inzitari et al., 2009 , Van Dijk et al., 2008 ). To date, only few studies have investigated the association between WMH and physical frailty ( Avila-funes et al., 2017 , Chen et al., 2015 , Chung et al., 2016 , Del Brutto et al., 2017 , Siejka et al., 2017 ), of which only 2 studies have assessed WMH quantitatively ( Avila-funes et al., 2017 , Chen et al., 2015 ). The association between physical frailty and WMH is unclear, as 3 previous studies found no association between WMH and frailty ( Chen et al., 2015 , Chung et al., 2016 , Del Brutto et al., 2017 ), and only one study did find an association ( Avila-funes et al., 2017 , Siejka et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying the development of this condition are complex, but seem to include a decrease in brain health . To date, many studies have reported cross‐sectional and prospective associations between brain health and frailty. Markers of cerebral damage, which are used to measure brain health and that are precursors of future dementia, were found to be associated with frailty: brain amyloid load and white matter lesions (WMLs) .…”
Section: Introductionmentioning
confidence: 99%
“…22 Indeed, poststroke delirium is thought to result from patient's cognitive frailty related to prestroke cognitive impairment which is exacerbated by the physical disability and biochemical changes related to the acute brain insult. Del Brutto et al 23 recently suggested that brain cortical volume could be an magnetic resonance imaging marker of this cognitive frailty. In line with this hypothesis, Oldenbeuving et al 24 reported that global cortical atrophy was an independent predictor of acute delirium.…”
Section: Discussionmentioning
confidence: 99%